Visual quotes: Does aesthetic appeal influence how perceived motivating text messages impact short-term exercise motivation? - Duro, Lígia; Romão, Teresa; Campos, Pedro F.; Karapanos, Evangelos (My University, 2019)
Visual Quotes, or the communication of motivational text messages in a visual format, are increasingly used across social media and online communities. While physical activity trackers could leverage visual quotes, empirical studies of activity tracking in HCI research have paid little attention to this phenomenon and their potential effects on motivation. In this work, we conducted an online experiment (129 participants) to evaluate the impact of aesthetic appeal in motivational text messages as it relates to extrinsic identified behavior regulation. This is the type of motivation linked to the initial adoption of exercise behavior. The results of our study demonstrate that a perceived motivating text message presented with different levels of aesthetic appeal - ugly, neutral, beautiful - has the same impact on the motivation linked to short-term exercise (extrinsic identified behavior regulation). In other words, the perceived aesthetic appeal did not influence the motivating capability of textual messages for encouraging physical activity.
Keywords: Visual Quotes; Motivational Text Messages; Aesthetic Appeal; Physical Exercise Motivation